Characterization of NAC transcription factor NtNAC028 as a regulator of leaf senescence and stress responses - Wen, Lichao; Liu, Tao; Deng, Zhichao; Zhang, Zenglin; Wang, Qi; Wang, Weifeng; Li, Wei; Guo, Yongfeng (Frontiers in Plant Science, 2022)
NAC proteins constitute one of the largest transcription factor families and are involved in regulation of plant development and stress responses. Our previous transcriptome analyses of tobacco revealed a significant increase in the expression of NtNAC028 during leaf yellowing. In this study, we found that NtNAC028 was rapidly up-regulated in response to high salinity, dehydration, and abscisic acid (ABA) stresses, suggesting a vital role of this gene in abiotic stress response. NtNAC028 loss-of-function tobacco plants generated via CRISPR-Cas9 showed delayed leaf senescence and increased tolerance to drought and salt stresses. Meanwhile NtNAC028 overexpression led to precocious leaf senescence and hypersensitivity to abiotic stresses in Arabidopsis, indicating that NtNAC028 functions as a positive regulator of natural leaf senescence and a negative regulator of stress tolerance. Furthermore, NtNAC028-overexpressing Arabidopsis plants showed lower antioxidant enzyme activities, higher reactive oxygen species (ROS) and H2O2 accumulation under high salinity, resulted in more severe oxidative damage after salt stress treatments. On the other hand, NtNAC028 mutation in tobacco resulted in up-regulated expression of ROS-scavenging and abiotic stress-related genes, higher antioxidant enzyme activities, and enhanced tolerance against abiotic stresses, suggesting that NtNAC028 might act as a vital regulator for plant stress response likely by mediating ROS scavenging ability and/or other stress tolerance pathways. Collectively, our results indicated that the NtNAC028 plays a key regulatory role in leaf senescence and response to multiple abiotic stresses.